Sox7 Plays Crucial Roles in Parietal Endoderm Differentiation in F9 Embryonal Carcinoma Cells through Regulating Gata-4 and Gata-6 Expression - Futaki, Sugiko (American Society for Microbiology, 2004)
During early rodent development, the parietal endoderm appears from an inner cell mass and produces large amounts of basement membrane components, such as laminin-1 and collagen IV. To elucidate the regulatory network for gene expression during these procedures, we constructed a series of short interfering RNA expression vectors targeted to various transcription factors, transfected them into F9 embryonal carcinoma cells, and evaluated the effects of the gene silencing on the induction of parietal endoderm differentiation and basement membrane component production by treating F9 cells with all trans-retinoic acid and dibutyryl cyclic AMP. Among the transcription factors tested, silencing of Sox7 or combined silencing of Gata-4 and Gata-6 resulted in suppression of cell shape changes and laminin-1 production, which are the hallmarks of parietal endoderm differentiation. In cells silenced for Sox7, induction of Gata-4 and Gata-6 by retinoic acid and cyclic AMP treatment was inhibited, while induction of Sox7 was not affected in cells silenced for Gata-4 and Gata-6, indicating that Sox7 is an upstream regulatory factor for these Gata factors. Nevertheless, silencing of Sox7 did not totally cancel the action of retinoic acid, since upregulation of coup-tf2, keratin 19, and retinoic acid receptor β2 was not abolished in Sox7-silenced F9 cells. Although overexpression of Sox7 alone was insufficient to induce parietal endoderm differentiation, overexpression of Gata-4 or Gata-6 in Sox7-silenced F9 cells restored the differentiation into parietal endoderm. Sox7 is therefore required for the induction of Gata-4 and Gata-6, and the interplay among these transcription factors plays a crucial role in parietal endoderm differentiation.